Tunable Pseudocapacitive Intercalation of Chloroaluminate Anions into Graphite Electrodes for Rechargeable Aluminum Batteries. Issue 6 (8th June 2021) - Xu, Jeffrey H.; Schoetz, Theresa; McManus, Joseph R.; Subramanian, Vikesh R.; Fields, Peter W.; Messinger, Robert J.
Abstract : Rechargeable aluminum-graphite batteries using chloroaluminate-containing electrolytes have been the focus of significant research, particularly due to their high-rate capabilities. Engineered graphite electrodes have been shown to exhibit supercapacitor-like rate performance, despite the fact they store charge via the electrochemical intercalation of polyatomic AlCl4 − anions. However, the origins of such rate capabilities are not well understood. Here, using electrochemical techniques, we disentangle quantitatively the diffusion-limited Faradaic, pseudocapacitive, and capacitive contributions to charge storage, revealing that AlCl4 − anions intercalate into graphite with significant pseudocapacitive characteristics due to low ion diffusion limitations. Pristine and mildly exfoliated graphites are compared, where exfoliation resulted in significantly higher pseudocapacitive AlCl4 − intercalation at the highest potential redox pair as well as higher galvanostatic capacity retention at faster discharge rates. The relationships between graphite structure, ion mass transport, and the overall rate of electrochemical AlCl4 − intercalation are discussed. Ion diffusion within the electrolyte phase of the porous electrode is shown to play a key role in controlling the rate of intercalation at higher potentials and faster rates, which can be enhanced by reducing electrode tortuosity. The results establish that chloroaluminate anion intercalation into graphite exhibits non-diffusion-limited pseudocapacitive contributions that are tunable by modifying the graphite structure.